Penerapan Sanksi Pidana dan Perlindungan Hukum Korban Tindak Pidana Lingkungan Hidup Oleh Korporasi - Ika Handayani Paturu; Aullia Vivi Yulianingrum (CV Putra Publisher, 2023)
The purpose of this study was to describe and analyze the effectiveness of the implementation of criminal sanctions against corporations, to find out the legal basis that protects victims of environmental crimes by corporations, and the legal protection provided by positive law to victims of environmental crimes committed by corporations. The method used in this research is normative legal research which then uses two approaches, namely the Legislation approach and the case study approach. With data collection techniques in this study through analysis of legal norms in laws and regulations using deductive reasoning logic. The results of this study conclude that in principle the imposition of criminal sanctions is currently considered not fully effective to be applied to corporations so that legal protection of the rights of victims of environmental crimes is not realized properly, followed by other sanctions such as without ending environmental restoration sanctions such as reclamation. and compensation.